Attack of the 50-foot cupid - Benton, Jim. (New York : Simon & Schuster Books for Young Readers, 2004)
When Franny's new lab assistant turns out to be all thumbs --or all paws--and accidentally loses a giant, fifty-foot, arrow-shooting cupid, it is entirely up to Franny to save the day.
Bklst 03/01/2004
SLJ May 2004
PW 12/15/2003
2-3
Keywords: Monsters -- Fiction; Science -- Experiments -- Fiction; Schools -- Fiction; Humorous stories